(-)-T-Cadinol—a Sesquiterpene Isolated From Casearia sylvestris (Salicaceae)—Displayed In Vitro Activity and Causes Hyperpolarization of the Membrane Potential of Trypanosoma cruzi - dos Santos, Augusto L.; Amaral, Maiara; Hasegawa, Flavia Rie; Lago, João Henrique G.; Tempone, Andre G.; Sartorelli, Patricia (Frontiers in Pharmacology, 2021)
Chagas disease is caused by the protozoan parasite Trypanosoma cruzi and affects 6–8 million people worldwide, mainly from developing countries. The treatment is limited to two approved nitro-derivatives, nifurtimox and benznidazole, with several side effects and reduced efficacy. Casearia sylvestris has been used in folk medicine as an antiseptic and cicatrizing in skin diseases. In the present work, the hexane phase from the MeOH extract from the leaves of Casearia sylvestris afforded a fraction composed by the sesquiterpene T-cadinol, which was chemically characterized by NMR and HRMS. The activity of T-cadinol was evaluated against T. cruzi, and IC50 values of 18 (trypomastigotes) and 15 (amastigotes) µM were established. The relation between the mammalian toxicity and the antiparasitic activity resulted in a selectivity index >12. Based on this promising activity, the mechanism of action was investigated by different approaches using fluorescent-based techniques such as plasma membrane permeability, plasma membrane electric potential, mitochondrial membrane electric potential, reactive oxygen species, and the intracellular calcium (Ca2+) levels. The obtained results demonstrated that T-cadinol affected neither the parasite plasma membrane nor the electric potential of the membrane. Nevertheless, this compound induced a mitochondrial impairment, resulting in a hyperpolarization of the membrane potential, with decreased levels of reactive oxygen species. No alterations in Ca2+ levels were observed, suggesting that T-cadinol may affect the single mitochondria of the parasite. This is the first report about the occurrence of T-cadinol in C. sylvestris, and our data suggest this sesquiterpene as an interesting hit compound for future optimizations in drug discovery studies for Chagas disease.